Perancangan Sistem Drainase Yang Efektif Guna Mengatasi Masalah Banjir Pada Daerah Bundaran Tank Jalan Martandu Kota Kendari - Annisa Puji Lestari Thahir; hujiyanto Hujiyanto; Rizaldi Wahab Dharmawan (Universitas Sulawesi Tenggara, 2026)
Flooding is a natural phenomenon that often causes significant losses, influenced by both natural factors and human activities. One of the flood-prone areas is Martandu Street in Kendari, Southeast Sulawesi. This study aims to analyze the drainage capacity along a 1,550 m channel using a quantitative approach based on rainfall data, channel measurements, and hydrological analysis. The results show that the design discharge (4.298 m³/s) exceeds the existing channel capacity (2.913 m³/s), indicating that the drainage system can only accommodate 68% of runoff from a 305.495 ha catchment area. To address this issue, a redesign of the channel was proposed with improved dimensions. The redesigned channel is capable of accommodating a discharge of 4.301 m³/s, ensuring effective drainage performance and reducing flood risk in the area.